Initiatives to prevent spread of infectious diseases in public health centers: Experience from positive case among health workers in COVID-19 pandemic - Novriana, Riska; Febe, Ester; Hasanbasri, Mubasysyir; Wibawa, Tri; Emilia, Ova (BKM Public Health and Community Medicine, 2021)
Several public health center temporary closures due to antigen positive health workers in Daerah Istimewa Yogyakarta have been reported. Behind the scene, there was confusion among health workers when they were not sure about sources of transmission and concerns about wider transmission among health workers and their families. This paper reports the Yogyakarta City Health Office initiative to build health workers’ awareness and to protect health centers protected from transmitting all contagious conditions in the future, learning from the experience of the covid 19 pandemic. Kota Yogyakarta Health authority and Universitas Gadjah Mada held two focus group discussions to document (1) the experience of responding to cases of reactive antigens in health workers who need to receive future follow-up from the experiences of 18 puskesmas heads and elements of the health office, and (2) the puskesmas Covid 19 screening and testing capacity for the community and health personnel use. This report raises the importance of safe workplace operational rules that prevent disease transmission and urgent actions to enforce these rules in puskesmas and health offices.